Implementasi Sosialisasi Pemanfaatan Kecerdasan Buatan untuk Menciptakan Perangkat Pembelajaran yang Menarik dan Efektif di TKIT, SDIT, dan SMPIT Darut Tauhid Kabupaten Grobogan (Jurnal Pelayanan Masyarakat, 2025)
This community service activity aims to provide outreach and training related to the use of Artificial Intelligence (AI) in developing engaging, interactive, and effective learning tools for teachers in TKIT, SDIT, and SMPIT Darut Tauhid in Grobogan Regency. This service was carried out on June 11, 2025, using a qualitative approach through various methods, including presentations, interactive discussions, workshops, and direct practice in the use of AI technology. This activity emphasized improving teachers' skills in integrating AI technology into the learning process so that it can support the creation of a more innovative learning atmosphere and suit the needs of students in the digital era. The results of the activity showed a significant increase, both in terms of efficiency and quality. Teachers were able to save up to 70% of time preparing learning tools, produce more varied and engaging learning media, and show higher motivation in adopting digital technology to support the teaching and learning process. The three main tools introduced, namely ChatGPT, Claude, and Canva Magic Design, have been proven to help teachers in creating materials, designing media, and managing learning more effectively. The positive response from training participants also confirmed that the use of AI has significant potential for wider implementation in Islamic educational institutions. Therefore, this activity not only contributes to improving teacher competency but also opens up opportunities for developing technology-based learning models relevant to future educational challenges.